2013
DOI: 10.1371/journal.pone.0059800
|View full text |Cite
|
Sign up to set email alerts
|

Ras-Association Domain of Sorting Nexin 27 Is Critical for Regulating Expression of GIRK Potassium Channels

Abstract: G protein-gated inwardly rectifying potassium (GIRK) channels play an important role in regulating neuronal excitability. Sorting nexin 27b (SNX27b), which reduces surface expression of GIRK channels through a PDZ domain interaction, contains a putative Ras-association (RA) domain with unknown function. Deleting the RA domain in SNX27b (SNX27b-ΔRA) prevents the down-regulation of GIRK2c/GIRK3 channels. Similarly, a point mutation (K305A) in the RA domain disrupts regulation of GIRK2c/GIRK3 channels and reduces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…This phenomenon has been observed in Rap1-interacting adaptor molecule (RIAM), which contains both Rasassociation and PH domains and requires both Rap1 GTPase interaction, mediated by the Ras-association domain, and PtdInsP binding, mediated by the PH domain, for cell surface recruitment in activated T-cells (Wynne et al, 2012). The previous findings showing that SNX27 can associate with a small GTPase through its Ras-association-domain-related F1 module (Balana et al, 2013;Ghai et al, 2013;Loo et al, 2014), and the discovery here that it can bind PtdInsP species through the F3 module present a tempting parallel to the RIAM system, and suggests that PtdInsP, cargo and GTPase interactions may co-operatively contribute to membrane localization of SNX27 following certain cell stimuli.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…This phenomenon has been observed in Rap1-interacting adaptor molecule (RIAM), which contains both Rasassociation and PH domains and requires both Rap1 GTPase interaction, mediated by the Ras-association domain, and PtdInsP binding, mediated by the PH domain, for cell surface recruitment in activated T-cells (Wynne et al, 2012). The previous findings showing that SNX27 can associate with a small GTPase through its Ras-association-domain-related F1 module (Balana et al, 2013;Ghai et al, 2013;Loo et al, 2014), and the discovery here that it can bind PtdInsP species through the F3 module present a tempting parallel to the RIAM system, and suggests that PtdInsP, cargo and GTPase interactions may co-operatively contribute to membrane localization of SNX27 following certain cell stimuli.…”
Section: Discussionmentioning
confidence: 82%
“…In fact the b2 integrin subunit of LFA-1 has been shown to bind SNX27 in vitro in peptide arrays (Ghai et al, 2013). Furthermore, the interaction of SNX27 with cytoplasmic signaling molecules, including small GTPases (Balana et al, 2013;, diacylglycerol kinase f (DGKf) (Rincón et al, 2011;Rincón et al, 2007), and cytohesinassociated scaffolding protein (CASP) , suggests that it has an additional or related role in the scaffolding of signaling complexes.…”
Section: Discussionmentioning
confidence: 99%
“…The recombinant extension in the N terminus, either His-tags (49), large fluorescent proteins (20,50,51), or small oligopeptide tags for antibody staining (52), are generally considered to have little impact on biological functions (53)(54)(55). We find that a hexahistine tag on the N terminus of 6His-Ras(C181) slightly shifts the measured dimer K d (to 344 ± 28 molecules/μm 2 ) without changing the qualitative behavior of H-Ras dimerization (Fig.…”
Section: The Equilibrium Dissociation Constant For H-ras Dimerization Onmentioning
confidence: 82%
“…A more detailed analysis of β2-adrenergic receptor recycling revealed that sorting nexin 27 (SNX27) links β2-adrenergic receptors to the retromer tubule, which is important for recycling back to the plasma membrane (Temkin et al, 2011). In addition to the PDZ domain and PX domain, SNX27 contains a RA / FERM domain that is proposed to bind Ras-like GTPase proteins (Balana et al, 2013; Ghai et al, 2011); perhaps the RA domain recruits additional binding partners to regulate interaction with the retromer complex and trafficking from the early endosome. Using a proteomics approach, Steinberg et al (2013) discovered over 100 cell surface proteins that required a SNX27–retromer to prevent lysosomal degradation and maintain surface levels.…”
Section: Discussionmentioning
confidence: 99%